Manfred Bierwisch: Linguistics, Poetics, Aesthetics (ENTHYMEMA, 2010)
The paper briefly summarizes the proposal made in 1965 that "Poetic Competence" is the basis for creating and evaluating poetry. That this competence lives on, but is different from linguistic competence is exemplified by a close look at the segmental and supra-segmental, morpho-syntactic, lexical, and conceptual structure of Hölderlin's poem An Zimmern,  revealing a surprisingly complex and balanced structure of the apparently simple four lines. The second part of the paper discusses the question whether judgments about poetry are to be studied as based on the relation between specific properties of poems and persons. Finally the problem is raised, whether literary art is based on a specific Poetic Competence, or instantiates a general aesthetic ability applied to linguistic objects. This is construed as a speculative, but still empirical question.